2019
DOI: 10.1128/aac.01092-19
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of LN-1-255 in Combination with Imipenem in Severe Infection Caused by Carbapenem-Resistant Acinetobacter baumannii

Abstract: The carbapenem-hydrolyzing class D β-lactamases (CHDLs) are the main mechanism of carbapenem resistance in Acinetobacter baumannii. CHDLs are not effectively inactivated by clinically available β-lactam-type inhibitors. We have previously described the in vitro efficacy of the inhibitor LN-1-255 in combination with carbapenems. The aim of this study was to compare the efficacy of LN-1-255 with that of imipenem in murine pneumonia using A. baumannii strains carrying their most extended carbapenemases, OXA-23 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In recent years, our research group has been exploring the therapeutic potential of 6-arylmethylidene penicillin-based sulfones as new β-lactamase inhibitors that could recover antibiotic efficacy (Figure A) . This research has demonstrated the efficacy of the 2-pyridylmethylidene derivative 1 (LN-1-255) against the relevant carbapenemase OXA-48 and against all of the carbapenem-hydrolyzing class D β-lactamases of the pathogen Acinetobacter baumannii, which also displayed good efficacy in preclinical models of murine pneumonia . The key structural features responsible for the effectiveness of compound 1 relative to other penicillin-based sulfones (sulbactam, tazobactam) are (i) the catechol moiety (siderophore), which improves internalization through bacterial iron uptake pathways, and (ii) the 2-pyridylmethylene group, which can generate an indolizine adduct II that is resistant to hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our research group has been exploring the therapeutic potential of 6-arylmethylidene penicillin-based sulfones as new β-lactamase inhibitors that could recover antibiotic efficacy (Figure A) . This research has demonstrated the efficacy of the 2-pyridylmethylidene derivative 1 (LN-1-255) against the relevant carbapenemase OXA-48 and against all of the carbapenem-hydrolyzing class D β-lactamases of the pathogen Acinetobacter baumannii, which also displayed good efficacy in preclinical models of murine pneumonia . The key structural features responsible for the effectiveness of compound 1 relative to other penicillin-based sulfones (sulbactam, tazobactam) are (i) the catechol moiety (siderophore), which improves internalization through bacterial iron uptake pathways, and (ii) the 2-pyridylmethylene group, which can generate an indolizine adduct II that is resistant to hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility assays involving strains harboring the most common CHDLs in this species demonstrated the effectivity of LN-1-255, successfully placing the carbapenems MIC below the resistance clinical breakpoints and, together with inhibition kinetics and docking assays, identifying LN-1-255 as a pan-inhibitor of all A. baumannii CHDLs [ 22 ]. Moreover, LN-1-255 was able to significantly reduce the bacterial load in the lungs of mice infected with carbapenem-resistant A. baumannii strains (carrying either OXA-23 or OXA-24/40) relative to imipenem monotherapy when administered at a dose of 50 mg/kg q3h [ 23 ]. Therefore, our results, not only restoring the susceptibility of imipenem but also meropenem in a collection of Acinetobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, we observed that relative to tazobactam and avibactam, LN-1-255 wields significant in vitro inhibitory activity against isogenic A. baumannii strains carrying OXA-23, OXA-24/40, OXA-58, OXA-143, and OXA-235 CHDLs enzymes, displaying LN-1-255 approximately three logs higher affinity for CHDLs ( K I ) than comparators [ 22 ]. Murine pneumonia models were likewise used to test the in vivo performance of this penicillin sulfone inhibitor, with promising results being obtained in terms of toxicity and reduction of the bacterial burden relative to imipenem monotherapy in mice [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This compound has a K i value of 700 nM against A. baumannii OXA-24/40. Moreover, LN-1-255 demonstrated excellent microbiological synergy and inhibition kinetics parameters against diverse carbapenem-hydrolyzing class D β-lactamases in A. baumannii , including OXA-23, OXA-24/40, OXA-58, OXA-143, OXA-235, the chromosomally encoded OXA-51, and K. pneumoniae OXA-48, and a significantly higher activity than tazobactam and avibactam. , As revealed by the crystal structure of the OXA-24/40/ 72b enzyme adduct (PDB entry 3FZC, 2.0 Å), the flexible chain of the modified ligand is anchored in the active site by strong electrostatic and hydrogen bonding interactions between the sulfinate group and the carbamoyl group of the inhibitor and diverse polar residues within the pocket (Ser128, Lys218, Ser219, Ser128, Arg261) (Figure D). , The in vivo evaluation of the therapeutic efficacy of LN-1-255 in combination with imipenem, in an experimental murine pneumonia model caused by carbapenem-resistant A. baumannii transformants and clinical isolates carrying carbapenem-hydrolyzing class D β-lactamases, showed that this combination provides higher protection against pneumonia than the treatment with imipenem alone . LN-1-255 causes decreases in the MIC values of imipenem of between 32- and 128-fold.…”
Section: Penicillin-based Sulfonesmentioning
confidence: 93%